If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6r-3-r=-7(r+5)+8(2r-1)
We move all terms to the left:
6r-3-r-(-7(r+5)+8(2r-1))=0
We add all the numbers together, and all the variables
5r-(-7(r+5)+8(2r-1))-3=0
We calculate terms in parentheses: -(-7(r+5)+8(2r-1)), so:We get rid of parentheses
-7(r+5)+8(2r-1)
We multiply parentheses
-7r+16r-35-8
We add all the numbers together, and all the variables
9r-43
Back to the equation:
-(9r-43)
5r-9r+43-3=0
We add all the numbers together, and all the variables
-4r+40=0
We move all terms containing r to the left, all other terms to the right
-4r=-40
r=-40/-4
r=+10
| -4x=-½(10x+18) | | x^2+20x-441=0 | | 6(4x+1)=782.2(x+10)=60 | | -n=7.9 | | -200=-20n | | 9/5=x/5 | | p+147=299 | | (r+50)=r2+80 | | 14=v/8+2 | | -9-2x=5x-86 | | (3-4)2=9x2-+16 | | d-35=95 | | 2d+1/6=6(1/3d+2) | | 3(+4)=5x-1 | | 2.3z-6=8+2.3z | | -11r=385 | | 10+x=3x-32 | | -2(a+3)=18 | | -94=v-594 | | -2(n-1)+5=7(1-n) | | 4x+x+8=6-3x | | (X-1)^2+3x=0 | | 6+c=11 | | 17t+5t-9t-19t+20t=-14 | | -2m=-2m+6(7-m) | | d/(-3)=0.76 | | 12(7-2v+5v=-68 | | 33/4x=57 | | m+m-2m+5m-2=18 | | 7+x-4=20 | | 75=4y-1 | | 7p−15=83 |